2021
DOI: 10.1200/jco.2021.39.15_suppl.5542
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of mirvetuximab soravtansine (MIRV) and gemcitabine (G) in patients (Pts) with selected frα-positive solid tumors: Results in the ovarian cancer (EC) cohort.

Abstract: 5542 Background: Mirvetuximab soravtansine (MIRV) is an ADC comprising a FRα-binding antibody, cleavable linker, and the maytansinoid DM4, a potent tubulin-targeting agent. MIRV has promising single agent activity in FRα-positive medium/high expression epithelial ovarian cancer (EOC), at 6 mg/kg, based on adjusted ideal body weight (AIBW) IV every (q) 21 days. This study evaluated MIRV and G in recurrent EOC, endometrial and triple negative breast cancer. The recommended phase 2 dose (RP2D) was established at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, our meta-analysis is the rst article evaluating the e cacy and safety of MIRV in solid tumors. Since the drug itself has been used in clinical settings for a relatively short time and has been approved by the FDA through an accelerated process [30], most of the clinical trials we collected were single-arm trials [21][22][23][24][25][26][27][28][29], which may have slightly lower quality evidence. Nevertheless, our analysis still yielded relatively encouraging results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, our meta-analysis is the rst article evaluating the e cacy and safety of MIRV in solid tumors. Since the drug itself has been used in clinical settings for a relatively short time and has been approved by the FDA through an accelerated process [30], most of the clinical trials we collected were single-arm trials [21][22][23][24][25][26][27][28][29], which may have slightly lower quality evidence. Nevertheless, our analysis still yielded relatively encouraging results.…”
Section: Discussionmentioning
confidence: 99%
“…There were a variety of study designs, including 1 randomized controlled trial [21], 7 single-arm studies [22][23][24][25][26][27][28][29] and 1 multiarm study [24], which provided two records for analysis. The patients who participated in these studies primarily had gynecological cancer, and many of them had prior cancer treatment, with some even having con rmed platinum resistance.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the cohort of 30 patients with recurrent FRα-positive platinum-resistant OC (53% had prior PARPi), the ORR was 36.7% with a median PFS of 5.4 months. 91 A second phase I trial enrolled five patients with recurrent endometrial cancer and 13 with OC, of which five had received prior PARPi; the ORR achieved with mirvetuximab and rucaparib was 40% and median PFS of 12.6 months in those with OC. 92 Pivotal information from the SORAYA trial reported an ORR of 32.4% in 105 patients, with a median duration of response (DOR) of 6.9 months and PFS of 4.3 months.…”
Section: Reviewmentioning
confidence: 99%